Comparative analysis of solvent-based and solvent-free (melting) methods for fabricating 3D-printed polycaprolactone-hydroxyapatite composite bone scaffolds: physicochemical/mechanical analyses and in vitro cytocompatibility - De Vega, Brigita; Dutta, Abir; Mumtaz, Aisha; Schroeder, Bob C.; Gerrand, Craig; Boyd, Ashleigh S.; Kalaskar, Deepak M. (Frontiers in Bioengineering and Biotechnology, 2025)
PurposeThe study conducts a comparative analysis between two prominent methods for fabricating composites for bone scaffolds—the (solid) solvent method and the solvent-free (melting) method. While previous research has explored these methods individually, this study provides a direct comparison of their outcomes in terms of physicochemical properties, cytocompatibility, and mechanical strength. We also analyse their workflow and scalability potentials.Design/methodology/approachPolycaprolactone (PCL) and hydroxyapatite (HA) composites were prepared using solvent (chloroform) and melting (180°C) methods, then 3D-printed using an extrusion-based 3D printer to fabricate scaffolds (8 × 8 × 4 mm). Rheology, scanning electron microscopy (SEM), energy-dispersive X-ray spectroscopy (EDX), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), accelerated degradation, mechanical/compression test, wettability/contact angle, live/dead assay, and DNA quantification (Picogreen) assays were evaluated.FindingsThe study finds that scaffolds made via the solid solvent method have higher mechanical strength and degradation rate as compared to those from the melting method, while both methods ensure adequate cytocompatibility and homogenous hydroxyapatite distribution, supporting their use in bone tissue engineering.OriginalityThis research investigates the utility of chloroform as a solvent for PCL composite in a direct comparison with the melting method. It also highlights the differences in workflows between the two methods and their scalability implications, emphasizing the importance of considering workflow efficiency and the potential for automation in scaffold fabrication processes for bone tissue engineering applications.